Novel Protective Role for Ubiquitin-Specific Protease 18 in Pathological Cardiac Remodeling. Issue 5 (November 2016) - Ying, Xiaoying; Zhao, Yichao; Yao, Tianbao; Yuan, Ancai; Xu, Longwei; Gao, Lingchen; Ding, Song; Ding, Hongyi; Pu, Jun; He, Ben
Abstract : Ubiquitin-specific protease 18 (USP18), a USP family member, is involved in antiviral activity and cancer inhibition. Although USP18 is expressed in heart, the role of USP18 in the heart and in cardiac diseases remains unknown. Here, we show that USP18 expression is elevated in both human dilated hearts and hypertrophic murine models. Cardiomyocyte-specific overexpression of USP18 in mice significantly blunted cardiac remodeling as evidenced by mitigated myocardial hypertrophy, fibrosis, ventricular dilation, and preserved ejection function, whereas USP18-deficient mice displayed exacerbated cardiac remodeling under the same pathological stimuli. Similar results were observed for in vitro angiotensin II–induced neonatal rat cardiomyocyte hypertrophy. The antihypertrophic effects of USP18 under hypertrophic stimuli were associated with the blockage of the transforming growth factor-β–activated kinase 1-p38/c-Jun N-terminal kinase 1/2 signaling cascade. Blocking transforming growth factor-β–activated kinase 1-p38/c-Jun N-terminal kinase 1/2 signaling with a pharmacological inhibitor (5Z-7-oxozeaenol) greatly reversed the detrimental effects observed in USP18-knockout mice subjected to aortic banding. Our data indicate that USP18 inhibits cardiac hypertrophy and postpones cardiac dysfunction during the remodeling process, which is dependent on its modulation of the transforming growth factor-β–activated kinase 1-p38/c-Jun N-terminal kinase 1/2 signaling axis. Thus, USP18 is a potent therapeutic target for heart failure treatment. Abstract : Supplemental Digital Content is available in the text.